Synergetic effect of two halogen promoters present in acidic reaction medium or catalyst on the H2O2 formation (in H-2-to-H2O2 oxidation) and destruction over Pd/C (or Al2O3) catalyst - Choudhary, Vasant R.; Jana, Prabhas (Journal of Catalysis, 2007)
A strong synergetic effect of two different halide anions (F- and I-, Cl- and I-, Cl- and Br-, and F- and Br-) at optimum concentration in the catalyst or in an acidic reaction medium was observed in the H-2-to-H2O2 oxidation over Pd/C, Pd/Al2O3, and halogenated Pd/Al2O3 catalysts. The synergetic effect promote, the net H2O2 formation by inhibiting the H2O2 decomposition and hydrogenation reactions. The effect is most pronounced for the combination of fluoride (or chloride) and iodide anions. The Br (1 wt%)-F (1 wt%)-Pd (5 wt%)/Al2O3 catalyst showed very high H2O2 yield (59%)/selectivity (60%) in the H-2-to-H2O2 oxidation. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: H-2-to-H2O2 oxidation; H2O2 decomposition H2O2 hydrogenation; halogen promoter; Hydrogen peroxide; Pd/Al2O3; Pd/C; synergetic effect

Direct H(2)-to-H(2)O(2) oxidation in aqueous acidic medium containing Br promoter over Pd/Al(2)O(3) and Pd/C catalysts thermally pretreated under different conditions - Choudhary, Vasant R.; Jana, Prabhas; Bhargava, Suresh Kumar (Catalysis Letters, 2008)
Influence of thermal pretreatments (under N(2), air or H(2) gas atmosphere at 500 degrees C or 700 degrees C) has been investigated for the Pd/Al(2)O(3) and Pd/Carbon catalysts in terms of its effect on their Pd particle size and performance in the H(2)-to-H(2)O(2) oxidation and H(2)O(2) destruction (by decomposition and/or hydrogenation) reactions in aqueous acidic medium containing Br promoter. The influence on the net H(2)O(2) formation is found to depend strongly upon the catalyst support due to support-Pd cluster interactions. For both the catalysts, the thermal treatments (except in air) caused a large increase in their Pd particle size. The increase in Pd particle size caused an increase in the H(2)O(2) formation activity of Pd/Al(2)O(3) but a decrease in the H(2)O(2) formation activity of Pd/C.
Keywords: Hydrogen peroxide; oxidation of H(2) to H(2)O(2); Pd/Al(2)O(3); Pd/C